Can anyone show me how to solve this? g(x) = 10x^9 + 5x^3 10(g^-1(11))^9 + 5(g^-1(11))^3-9
Follow Math Help Forum on Facebook and Google+
What do you have to solve? (I can't see anything, maybe I'm the only one)
i posted a screenshot of the problem but i guess it didnt work. i wrote it out above
Originally Posted by bseymore Can anyone show me how to solve this? g(x) = 10x^9 + 5x^3 10(g^-1(11))^9 + 5(g^-1(11))^3-9 $\displaystyle g(x) = 10x^9 + 5x^3$ let $\displaystyle a$ be the real value such that $\displaystyle g(a) = 11$ since $\displaystyle g(a) = 11$ , $\displaystyle g^{-1}(11) = a$ $\displaystyle 10a^9 + 5a^3 - 9 = g(a) - 9 = 11 - 9 = 2$
Originally Posted by bseymore Can anyone show me how to solve this? g(x) = 10x^9 + 5x^3 10(g^-1(11))^9 + 5(g^-1(11))^3-9 For any (invertible) function g, $\displaystyle g(g^{-1}(x))= x$ Note that $\displaystyle 10x^9+ 5x^3- 9= g(x)- 9$.
thanks guys! I understand it now
View Tag Cloud